Evaluation of related factors in pulmonary edema and aspiration pneumonia among rice tablet poisonings - AF Fayaz (فصلنامه ابن سینا)
Abstract Background: Aluminum phosphide or rice tablet is a solid disinfectant that globally used to protect cereal crops from insects and rodents. However in recent years, due to its easy accessibility the youth used it for suicide. In this study, related factors in pulmonary edema and aspiration pneumonia among rice tablet poisonings were investigated. Materials and methods: This study examined the clinical records of 67 patients with acute oral toxicity as a result of consumption aluminum phosphide admitted in Bahrlo hospital as well as 28 files of autopsy in Kahrizak forensic research center. Recorded data included patients’ gender, aspiration pneumonia, and pulmonary edema. The data was analyzed using the software SPSS ver. 16. Results: All patients received standard conservative therapy. Out of 67 patients, 30 (%44.8) were male. A significant correlation was also found between patients’ age and aspiration pneumonia (p=0.035), so that the older patients have more possibility to engage the aspiration pneumonia. The mean age of patients with and without aspiration pneumonia was 36.75±14.45 and 24.92±10.43. In addition, the mortality risk was 1.5 times more in patients with pulmonary edema. Conclusion: Aluminum phosphide poisoning is a topical issue in public health. This study investigated some consequences of aluminum phosphide consumption. The results of this study can help to facilitate the prevention and treatment of rice tablet poisoning.